PERAN PENDIDIKAN KEWARGANEGARAAN DALAM MEMBANGUN KESADARAN LINGKUNGAN BERKELANJUTAN - Kamlasi, Anjulin Yonathan; Lamauran, Wilibrodus Manga; Lestari, Kasihani; Radja, Melinda Ratu (Jurnal Lazuardi, 2025)
This study aims to analyse the role of civic education in building sustainable environmental awareness among students. The research method used is qualitative with a literature study approach, namely by examining various scientific sources such as journal articles, books, previous research results, and relevant policy documents. The data were analysed descriptively through the stages of reduction, presentation, and conclusion drawing to obtain a comprehensive understanding of the relationship between PKn and the formation of ecological awareness. The results showed that civic education serves as a means of fostering moral attitudes, social responsibility, and ecological awareness among students. Civic education shapes civic knowledge, civic skills, and civic dispositions relevant to environmental issues, thereby fostering understanding, skills, and attitudes of concern for sustainable coexistence. In contextual and applied learning, such as project-based learning and the application of the Pancasila Student Profile, students can actively participate in recycling, greening, and energy conservation activities as a tangible manifestation of environmentally-conscious citizenship values. Effective strategies that can be implemented include the application of an eco-civic education approach, the strengthening of character education based on Pancasila values, and participatory learning that involves students in social action and ecological reflection. The benefits of implementing environment-based PKn include the formation of an environmentally conscious character, increased ecological literacy, and contribution to the achievement of the Sustainable Development Goals (SDGs).